Non-Anaemic Iron Deficiency in Female Patients: A Multicenter Study in Islamabad. - Qamar, Saima; Rauf, Raazia; Ejaz, Shazma; Riaz, Beenish; Iftikhar, Taqdees; Akhtar, Nazneen (Journal of Rawalpindi Medical College, 2026)
Objective: To assess the impact of iron status on fatigue levels in non-anemic female patients using the Fatigue Severity Scale. Methods: A Quasi-Experimental Study was conducted at the Department of Obstetrics and Gynaecology of Akhter Saeed Medical College, Farooq Hospital, and KRL Hospital, Islamabad, from 1st Oct 2023 to 30th Sept 2025. A total of 150 non-anaemic female patients (haemoglobin levels ≥12 g/dL in gynaecological patients and ≥11 g/dL in obstetric patients) were enrolled in the study after taking written informed consent. Fatigue was assessed using the Fatigue Severity Scale pre- and post-treatment. The primary outcome was the improvement in fatigue scores post-treatment with iron infusion. All the collected data were entered and analyzed through SPSS version 25. Results: The baseline mean fatigue severity score was 50.96 ± 10.3 in pregnant women, which, after intervention, considerably decreased to 23.76 ± 6. Likewise, the baseline mean fatigue severity scale was 52.12 ± 9 in gynaecological patients. After treatment, the level decreased to 23.42 ± 5.34. Both groups saw their fatigue scores drop markedly after the intervention, ending with similar results on the Fatigue Severity Scale. Conclusion: Even with normal haemoglobin levels, deficiency of iron can lead to higher fatigue in females. When ferric carboxymaltose is administered to iron-deficient females, it efficiently decreases the severity of fatigue, signifying the value of giving iron supplements in non-anaemic females with low iron stores. Keywords: anaemia, ferritin, haemoglobin, iron, iron deficiency.